PROFILE OF ESOPHAGUS NEOPLASMS RELATED TO THE CONSUMPTION OF ALCOHOLIC BEVERAGES: : ANALYSIS OF THE HOSPITAL RECORDS OF THE JOSÉ ALENCAR GOMES DA SILVA NATIONAL CANCER INSTITUTE - Alves da Silva, Helio; Ferreira dos Reis, Valdenice; Ferreira dos Santos, Lenice; Glória dos Santos, Paulielly; Brendaly Sátiro Barroso, Isália; Santos Silva, Keila; Luíza Leobas Moreira Nogueira, Ana (Health and Society, 2021)
Introduction: Esophageal neoplasia presents a high morbidity and mortality rate, associated with males and the esolist habit. Objective: to describe the profile of esophageal neoplasia related to alcohol consumption between 2015 and 2019 in Montes Claros, Minas Gerais, Brazil. Methods: A descriptive study of quantitative approach was conducted through data from patients diagnosed with esophageal neoplasia in hospital records of the José Alencar Gomes da Silva National Cancer Institute (INCA). Results and discussion: 525 cases of esophageal neoplasia were recorded in the period evaluated. Alcohol consumption was positive in 88.1% of the cases. Conclusion: The data indicate a positive relationship between alcohol consumption and esophageal neoplasia. These data should encourage the establishment of public policies for health education measures in relation to alcohol consumption and smoking habits.